ANALISIS PERINGATAN DINI KEBANGKRUTAN BANK UMUM SYARIAH DI INDONESIA PERIODE 2011 – 2015 - Kurnia Krisna Hari; Sa’adah Siddik; Didik Susetyo (AKUNTABILITAS, 2017)
This study aims to give empirical prove on the factors that affecting early warning bankruptcyof Islamic banking in Indonesia using RGEC method. The factors that are tested in this study are Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG), Return on Assets (ROA), Net Operating Margin (NOM), and Capital Adequacy Ratio (CAR). The sample of this study consists of 7 Islamic banking in Indonesia. The data used is the quartile report of financial statements and the GCG report while the statistical method used is panel regression.The result shows that Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Return On Assets (ROA), and Capital Adequacy Ratio (CAR) gives impact to the early warning bankruptcy of the Islamic banking, while Good Corporate Governance (GCG) and Net Operating Margin (NOM) does not have any effect on the early warning bankruptcy. This implies that GCG and NOM are not inline with the policy, theory and previous studies.